The role of trust in the resolution of conservation conflicts. (March 2016) - Young, Juliette C.; Searle, Kate; Butler, Adam; Simmons, Peter; Watt, Allan D.; Jordan, Andrew
Abstract: Conflicts between biodiversity conservation and other human activities are intensifying as a result of growing pressure on natural resources and concomitant demands by some for greater conservation. Approaches to reducing conflicts are increasingly focusing on engaging stakeholders in processes that are perceived as fair, i.e. independent and where stakeholders have influence, and which in turn can generate trust between stakeholders. Hitherto, there has been limited empirical research supporting the claim that conservation conflicts can be reduced by building trust through fair participation. Using quantitative and qualitative empirical data from three case studies, we analysed whether fair participation processes were directly related to conflict resolution and if this relationship was mediated by trust. Our research provided empirical quantitative evidence that increased trust through fair processes makes conflict resolution more likely. The qualitative analysis revealed caveats to this finding, including the different understandings of the definition of conflict by stakeholders, the complex nature of trust in conservation conflicts where most stakeholders have high levels of ecological knowledge, and the atypical nature (i.e. presence of a local champion) of one of the case studies. Building and maintaining trust with landowners and managers may be central to conserving biodiversity. Such trust-building requires effort and resources, opportunities for appropriate dialogue between stakeholders and a willingness to share power in terms of knowledge and policy implementation, especially when local stakeholders are dependent on and knowledgeable about natural resources.